Evaluation of the Edge Crack Torsion (ECT)Test for Mode III Interlaminar Fracture Toughness of Laminated Composites - Li, J.; Lee, S.M.Lee, E.W.; O'Brien, T.K.
An analytical and experimental investigation was cartied out on G40-800/R6376 graphite/epoxy laminates to evaluate the edge crack torsion (ECT)test as a candidate for a standard Mode III inteflaminar fracture toughness test for laminated composites. The ECT test consists of a [90/( +45)3/(-V-45)3190], laminate with a delamination introduced by a non-adhesive film at the mid-plane along one edge and loaded in a special fixture to create torsion along the length of the laminate. Dye penetrant enhanced X-radiograph of failed specimens revealed that the delamination initiated at the middle of the specimen length and propagated in a self-similar manner along the laminate midplane. A three-dimensional finite element analysis was performed that indicated that a pure Mode III delamination exists at the middle of specimen length away from both ends. At the ends near the loading point a small Mode II component exists. However, the magnitude of this Mode II strain energy release rate at the loading point is small compared to the magnitude of Mode HI component in the mid-section of the specimen. Hence, the ECT test yielded the desired Mode Ill delamination. The Mode III fracture toughness was obtained from a compliance calibration method that was in good agreement with the finite element results. Mode II end-notched flexure (ENF)tests and Mode I double cantilever beam (DCB)tests were also performed for the same composite material. The Mode I fracture toughness is much smaller than both the Mode II and Mode III fracture toughness. The Mode II fracture toughness is found to be 75
Keywords: COMPOSITE MATERIALS; FRACTURE TOUGHNESS; DELAMINATION; COMPLIANCE CALIBRATION; THREE-DIMENSIONAL FINITE ELEMENT ANALYSIS; STRAIN ENERGY RELEASE RATE